Art-Mimesis and Political Reality in Juan Carlos Tabío's El elefante y la bicicleta and Fernando Pérez's Suite Habana. Issue 1 (2nd January 2018) - Baker, Emily M.
ABSTRACT: This article uses the concept of art-mimesis to examine the reflections of two films, Juan Carlos Tabío's El elefante y la bicicleta and Fernando Pérez's Suite Habana, on the capacity of film to impact upon social reality in the context of the economic and political crises of the 1990s and early 2000s in Cuba. With reference to debates regarding the function of mimesis in the Cuban critical text The Viewer's Dialectic by Tomás Gutiérrez Alea, I argue that El elefante y la bicicleta retreats into fantasy, cutting itself off in a self-referential loop, and thus reflects the film industry's turmoil of the mid-1990s. Suite Habana, on the other hand, represents an adaptation to crisis in the form of cheaper production techniques, and a return of revolutionary ideals in the presentation of a scenario, whereby the division between art and labor could be eradicated.